Beliefs and attitudes of sevillians towards the chilean linguistic variety - Santana Marrero, Juana (Lenguas Modernas, 2023)
Following the methodology of the Project for the study of beliefs and attitudes towards the varieties of Spanish in the 21st century (PRECAVES XXI), the perception that Sevillians, speakers of the Andalusian variety, have of the Chilean dialect was analysed in this research. The results obtained from the survey of 108 subjects, distributed according to sex, age and educational level, showed that: 1) the Chilean variety was not included among the models of linguistic prestige contemplated by the respondents; 2) the degree of identification of this geolectal modality was low and it was often confused with the other Spanish-American varieties; 3) the direct and indirect valuations yielded rather positive beliefs and attitudes; and 4) sometimes, the social features of the respondents conditioned their opinions.